PENGARUH GREEN HUMAN RESOURCE MANAGEMENT TERHADAP KINERJA BERKELANJUTAN UMKM MELALUI KAPABILITAS INOVASI PADA SEKTOR PENGOLAHAN DI MAMMINASATA - Iwan Perwira; Hernita Hernita; Ahmad Ridha; Andi Faisal Syam; Baso Sardjan (Journal Economic Management and Business, 2026)
This study aims to examine the effect of Green Human Resource Management (GHRM) on the sustainable performance of SMEs by considering innovation capability as a mediating variable. The study is motivated by the increasing demand for SMEs to not only focus on economic performance but also address environmental and social sustainability issues. A quantitative approach with an explanatory design was employed, involving 170 SMEs in the processing sector in the Mamminasata region. Data were analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM). The results indicate that GHRM has a positive and significant effect on sustainable performance, both directly and indirectly through innovation capability. These findings suggest that environmentally orientated human resource management practices can foster innovation that contributes to improved business sustainability. Innovation capability serves as a key mechanism in strengthening this relationship, particularly through process improvements and operational efficiency. This study highlights that SME sustainability is not solely determined by business scale but also by the ability to manage human resources effectively and continuously develop innovation.